1985
DOI: 10.1161/01.res.57.4.562
|View full text |Cite
|
Sign up to set email alerts
|

Effects of reperfusion after coronary artery occlusion on post-infarction scar tissue.

Abstract: SUMMARY. Early reperfusion after a coronary occlusion may reduce myocardial infarct size, but late reperfusion into necrotic myocardium may alter post-infarction healing. In rabbits, we compared 1-or 3-week-old scars resulting from permanent coronary occlusion to those resulting from a 1-or 3-hour occlusion followed by reperfusion. Reperfusion at 1 hour post-occlusion did not affect scar mechanical properties assessed at 1 week post-infarction, but at 3 weeks postinfarction, these scars had a tensile strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 68 publications
1
23
0
1
Order By: Relevance
“…Our experiments quantitated increases in the mRNA for collagen I, III, and IV. Previous studies measured hydroxyproline and demonstrated no effect of reperfusion on collagen levels at 1 wk and beyond (5,39 (53,54). Histochemical data suggested fibronectin is deposited around myocytes in the early response to infarction (I15).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Our experiments quantitated increases in the mRNA for collagen I, III, and IV. Previous studies measured hydroxyproline and demonstrated no effect of reperfusion on collagen levels at 1 wk and beyond (5,39 (53,54). Histochemical data suggested fibronectin is deposited around myocytes in the early response to infarction (I15).…”
Section: Discussionmentioning
confidence: 96%
“…Changes in the extracellular matrix comprise an important part of the wound repair process, and this topic has been studied extensively, particularly with respect to collagen content and alterations in tensile strength and compliance (1)(2)(3)(4)(5). Fibronectin is an important component of the extracellular matrix that is thought to have a functional role in diverse cellular processes, including wound healing (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been previously shown that the tissue composition of a mature scar is an important determinant of its mechanical properties (Connelly et al 1985) and, thereby, can drastically influence overall ventricular performance …”
Section: Articlementioning
confidence: 99%
“…However, reperfusion therapy for the infarct-related artery is the most useful method of preventing dilatation of the infarcted myocardium that occurs during the early stage of AMI. [26][27][28][29] Because the tissue-healing process is enhanced by reperfusion therapy, 30) sufficient coronary arterial blood flow should be secured from the early stage of AMI. That is, PTCA with stenting may inhibit both the formation of peripheral embolism by debris with copious platelets 31) and patency maintenance in the infarct-related artery.…”
Section: Discussionmentioning
confidence: 99%